Tribological characterization of a labyrinth-abradable interaction in a turbo engine application - Delebarre, C.; Wagner, V.; Paris, J.Y.; Dessein, G.; Denape, J.; Gurt-Santanach, J. (Wear, 2017)
To enhance the efficiency of a turbo engine, one solution is reducing the clearance between the rotary parts in the secondary air system. This clearance reduction causes direct interactions in the secondary air system of a turbo engine when a rotary seal, called a labyrinth seal, rubs against the turbo engine casing as a result of successive starts and stops, thermal expansions and vibrations. To protect sealing systems from severe damage, abradable coatings are used on the inner periphery of the casing. The purpose of the present paper is to study the labyrinth-abradable interaction during high speed contacts through a detailed tribological characterization. The labyrinth-abradable interaction experiments were conducted on a dedicated test rig that was able to reproduce representative turbo engine operating conditions. A complete tribological analysis based on a third body approach and on accommodation flows was investigated using high speed imaging of the interaction. A schematic description of the interaction, with the addition of images extracted from recorded videos, is proposed to define two types of third body formation and their evolution during labyrinth-abradable interactions. Finally, the labyrinth-abradable interaction life cycle was used as a basis to discuss the coating subject to a labyrinth tip speed increase. •High speed test rig developed to simulate labyrinth seal-abradable interactions.•Identification of the wear mechanisms dynamic's using high speed imaging.•Tribological analysis based on a third body approach and on the accommodation flows.•Assessment of the mass balance based on a flow proportion estimate.•Discussion about the coating behaviour subjected to a labyrinth tip speed increase.